Eksistensi Dan Nilai-Nilai Kearifan Lokal Dalam Tari Silampari Kayangan Tinggi Di Kota Lubuklinggau - Memi Yuasti; Ira Miyarni S; Isbandiyah (Program Studi Pendidikan Sejarah - Universitas Samudra, 2025)
Traditional dance serves as a profound medium for preserving cultural identity and transmitting local wisdom across generations. This study explores the existence and embedded local values of Tari Silampari Khayangan Tinggi, a ceremonial welcome dance from Lubuklinggau City, South Sumatra, Indonesia. This study aims to describe the development of the Silampari Khayangan Tinggi Dance in 2025. and explain the local wisdom values ​​contained in the Silampari Khayangan Tinggi Dance. This study uses a qualitative descriptive approach with data collection techniques in the form of participatory observation, in-depth interviews, and documentation. The results of the study indicate that the Silampari Khayangan Tinggi Dance still has a strong existence, especially in the context of official ceremonies and local cultural diplomacy. However, the dynamics of social change and institutional limitations require systematic revitalization so that cultural values ​​are inherited intact, so that important steps to ensure the continuity of regional culture that is full of historical value and local wisdom. through education, innovation, and proper promotion, this dance can continue to live and become part of Indonesia's diverse cultural identity. This dance contains local wisdom reflected in the symbol of respect for guests (through the presentation of tepak sirih), aesthetics of make-up and movement that represent the gentleness of women, and local narratives such as the legend of Silampari and Dayang Torek.